Evidence for increased interferon type I activity in CD8+ T cells in giant cell arteritis patients - van Nieuwland, Marieke; Esen, Idil; Reitsema, Rosanne D.; Abdulahad, Wayel H.; van Sleen, Yannick; Jiemy, William F.; Sandovici, Maria; Brouwer, Elisabeth; van Bon, Lenny (Frontiers in Immunology, 2023)
Introduction: Giant cell arteritis (GCA) is a vasculitis of the medium- and large-sized arteries. Interferon type I (IFN-I) is increasingly recognized as a key player in autoimmune diseases and might be involved in GCA pathogenesis, however evidence is limited. IFN-I activates Janus kinase/signal transducers and activators of transcription (JAK-STAT) pathways, leading to increased expression of interferon stimulated genes. In this study, IFN-I activity in GCA is explored, focusing on CD8+ T cells. Methods: Expression of phospho-STAT (pSTAT) 1, 3 and 5 was investigated in IFN-α-stimulated peripheral mononuclear cells (PBMCs) gated separately for CD8+ T cells of patients with GCA (n=18), healthy controls (HC, n=15) and infection controls (n=11) by Phosphoflow method combined with fluorescent cell barcoding technique. Furthermore, IFN-I induced myxovirus-resistance protein A (MxA) and CD8+ T cell expression was investigated by immunohistochemistry in temporal artery biopsies (TAB) of GCA patients (n=20) and mimics (n=20), and in aorta tissue of GCA (n=8) and atherosclerosis patients (n=14). Results: pSTAT1 expression was increased in IFN-α stimulated CD8+ T cells from GCA patients, whereas no difference was observed in pSTAT3 and pSTAT5 expression. MxA was present in TABs of 13/20 GCA patients compared to 2/20 mimics and in 8/8 GCA+ compared to 13/14 GCA- aorta tissues. MxA location partially co-localized with CD8+T cell . Conclusions: Our results provide evidence for increased IFN-I activity in CD8+ T cells of GCA patients, both systemically and locally. These findings warrant further investigation regarding IFN-I induced biomarkers and IFN-I related novel therapeutic options in GCA.